Optimal Private and Public Harvesting under Spatial and Temporal Interdependence - Markku Ollikainen; Erkki Koskela (Center for Economic Studies and ifo Institute (CESifo), 2001)
This paper extends the Hartman model to include the case where two adjacent stands may be interdependent in the provision of amenity services. We show first that the relationship between the focal and exogenous rotation age depends on the nature of their temporal interdependence, i.e., on what happens to the degree of substitutability or complementarity between the stands when the rotation age of the private focal stand changes. We then apply this analysis to the determination of public rotation age in a two-stage game where the government first decides upon its harvesting and private harvesting is chosen in the second stage. Several new rules are derived for the socially optimal design of public harvesting depending on the nature of interdependence between private and public stands as well as on whether citizens have access to private forests for recreation or not.
Keywords: 330; Substitutability/complementarity; amenity valuation; private and public rotation age